Genetic and Phenotypic Landscape of Peripartum Cardiomyopathy. Issue 19 (11th May 2021) - Goli, Rahul; Li, Jian; Brandimarto, Jeff; Levine, Lisa D.; Riis, Valerie; McAfee, Quentin; DePalma, Steven; Haghighi, Alireza; Seidman, J. G.; Seidman, Christine E.; Jacoby, Daniel; Macones, George; et al.
Abstract : Background: Peripartum cardiomyopathy (PPCM) occurs in ≈1:2000 deliveries in the United States and worldwide. The genetic underpinnings of PPCM remain poorly defined. Approximately 10% of women with PPCM harbor truncating variants in TTN (TTNtvs). Whether mutations in other genes can predispose to PPCM is not known. It is also not known if the presence of TTNtvs predicts clinical presentation or outcomes. Nor is it known if the prevalence of TTNtvs differs in women with PPCM and preeclampsia, the strongest risk factor for PPCM. Methods: Women with PPCM were retrospectively identified from several US and international academic centers, and clinical information and DNA samples were acquired. Next-generation sequencing was performed on 67 genes, including TTN, and evaluated for burden of truncating and missense variants. The impact of TTNtvs on the severity of clinical presentation, and on clinical outcomes, was evaluated. Results: Four hundred sixty-nine women met inclusion criteria. Of the women with PPCM, 10.4% bore TTNtvs (odds ratio=9.4 compared with 1.2% in the reference population; Bonferroni-corrected P [ P *]=1.2×10 –46 ). We additionally identified overrepresentation of truncating variants in FLNC (odds ratio=24.8, P *=7.0×10 –8 ), DSP (odds ratio=14.9, P *=1.0×10 –8 ), and BAG3 (odds ratio=53.1, P *=0.02), genes not previously associated with PPCM. This profile is highly similar to that found in nonischemic dilated cardiomyopathy. Women with TTNtvs had lower left ventricular ejection fraction on presentation than did women without TTNtvs (23.5% versus 29%, P =2.5×10 –4 ), but did not differ significantly in timing of presentation after delivery, in prevalence of preeclampsia, or in rates of clinical recovery. Conclusions: This study provides the first extensive genetic and phenotypic landscape of PPCM and demonstrates that predisposition to heart failure is an important risk factor for PPCM. The work reveals a degree of genetic similarity between PPCM and dilated cardiomyopathy, suggesting that gene-specific therapeutic approaches being developed for dilated cardiomyopathy may also apply to PPCM, and that approaches to genetic testing in PPCM should mirror those taken in dilated cardiomyopathy. Last, the clarification of genotype/phenotype associations has important implications for genetic counseling. Abstract : Supplemental Digital Content is available in the text.